Changes in mental illness stigma over 30 years – Improvement, persistence, or deterioration?. Issue 1 (4th November 2022) - Schomerus, Georg; Schindler, Stephanie; Sander, Christian; Baumann, Eva; Angermeyer, Matthias C.
Abstract: Background: Large efforts have been made to erase the stigma of mental illness, but it is unclear whether they have succeeded on a population level. We examine how attitudes toward people with depression or schizophrenia have evolved in Germany since 1990, and whether there are different developments for both disorders. Methods: Using data from the three decades, four wave repeated cross-sectional representative population study in the "old" (western) states in Germany with surveys in 1990 ( n  = 2, 044), 2001 ( n  = 4, 005), 2011 ( n  = 1, 984), and 2020 ( n  = 2, 449), we calculate time-trends for social distance and emotional reactions toward someone with major depression or acute schizophrenia. Results: Social distance worsened in six out of seven situations for schizophrenia, whereas improving in two out of seven situations for depression. Emotions related to fear and uneasiness increased for schizophrenia, whereas tending to decrease for depression. Pro-social reactions like the desire to help increased for depression, but decreased for schizophrenia. Initially observed differences, favoring depression over schizophrenia, widened over the 30-year study period. For schizophrenia, the biggest negative changes occurred between 1990 and 2001, whereas some improvements with regard to depression occurred more recently. Conclusion: Contrary to expectations, stigma has become more severe regarding acute schizophrenia in Germany over the last 30 years, whereas only slightly improving for depression. The apparent normalization of mental health problems seems not to directly translate into improving attitudes toward people with severe mental illness. Re-focusing of anti-stigma efforts on people with severe mental illness seems necessary.